2014
DOI: 10.1037/a0036437
|View full text |Cite
|
Sign up to set email alerts
|

Unconscious conflicts in unconscious contexts: The role of awareness and timing in flexible conflict adaptation.

Abstract: Humans adapt to context-specific frequencies of response conflicts. Typically, the impact of conflict-inducing information is reduced in contexts with high compared to low frequency of conflict. We investigated how such context-specific conflict adaptation depends on awareness and timing of conflict-eliciting stimuli and conflict-signaling contexts. In a priming paradigm, we varied the visibility of the prime and whether the context is a feature of either prime or target. Concretely, the context was represente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 97 publications
4
41
3
Order By: Relevance
“…If anything, our results indicate that the CSPC effect does not depend on awareness, contrary to the conclusion of Heinemann et al (2009). This is in line with a recent study by Reuss et al (2014) where the visibility of primes was manipulated in several masked priming experiments, while the conflict context was determined by the format of either the prime or the target. By associating the context with either prime or target, they could furthermore investigate whether the temporal proximity between context information and conflict is of importance for unconscious cognitive control to occur.…”
Section: Discussionsupporting
confidence: 92%
“…If anything, our results indicate that the CSPC effect does not depend on awareness, contrary to the conclusion of Heinemann et al (2009). This is in line with a recent study by Reuss et al (2014) where the visibility of primes was manipulated in several masked priming experiments, while the conflict context was determined by the format of either the prime or the target. By associating the context with either prime or target, they could furthermore investigate whether the temporal proximity between context information and conflict is of importance for unconscious cognitive control to occur.…”
Section: Discussionsupporting
confidence: 92%
“…Whereas the weighting of stimulus dimensions is classically thought to reflect relatively stable processes implemented based on task instructions (Cohen et al, 1990;Miller & Cohen, 2001), the CSPC transfer effect demonstrates that dimension weighting varies as a function of stimulus experience. While other studies have demonstrated a CSPC effect for frequency-unbiased stimuli (King, Donkin, Korb, & Egner, 2012; Reuss, Desender, Kiesel, & Kunde, 2014;Weidler & Bugg, 2016), we know of no other report of a location-based CSPC transfer effect in the literature where the contribution of context and transfer sets can be independently estimated. In Experiment 1 we perform a direction replication of the context-level transfer manipulation used by Crump and Milliken (2009) and look for evidence that context-driven control generalizes to frequency-unbiased stimuli.…”
Section: Methodsmentioning
confidence: 82%
“…A first group of studies used subliminal stimulus presentation for investigating the role of awareness in CSPS effects, but obtained mixed results. Some studies suggest that CSPC effects require awareness (Heinemann, Kunde, & Kiesel, 2009) but others do not (Reuss, Desender, Kiesel, & Kunde, 2014;Schouppe, de Ferrere, Van Opstal, Braem, & Notebaert, 2014). In another study, Crump, Gong, and Milliken (2006) asked participants whether they were aware of the precise proportion manipulation following the experiment.…”
Section: Control-based Accounts Of the Lwpc Effectmentioning
confidence: 99%